2021
DOI: 10.3390/vaccines9091001
|View full text |Cite
|
Sign up to set email alerts
|

Preventive HIV Vaccines-Leveraging on Lessons from the Past to Pave the Way Forward

Abstract: Almost four decades on, since the 1980’s, with hundreds of HIV vaccine candidates tested in both non-human primates and humans, and several HIV vaccines trials later, an efficacious HIV vaccine continues to evade us. The enormous worldwide genetic diversity of HIV, combined with HIV’s inherent recombination and high mutation rates, has hampered the development of an effective vaccine. Despite the advent of antiretrovirals as pre-exposure prophylaxis and preventative treatment, which have shown to be effective,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(11 citation statements)
references
References 313 publications
(359 reference statements)
0
10
0
Order By: Relevance
“…The results published in 2021 indicated that this BnAb was unable to prevent overall HIV-1 acquisition, but that in VRC01-sensitive HIV-1 isolates, BnAb prophylaxis was effective [43]. The VRC01-sensitive HIV-1 isolates were only ~30% of the strains in circulation [44]. These results suggest that the VRC01 suppressed early circulating strains, but the immune system eventually lost to evolving resistant viral variants.…”
Section: Broadly Neutralizing Antibodies In Passive Immunization Trialsmentioning
confidence: 99%
See 4 more Smart Citations
“…The results published in 2021 indicated that this BnAb was unable to prevent overall HIV-1 acquisition, but that in VRC01-sensitive HIV-1 isolates, BnAb prophylaxis was effective [43]. The VRC01-sensitive HIV-1 isolates were only ~30% of the strains in circulation [44]. These results suggest that the VRC01 suppressed early circulating strains, but the immune system eventually lost to evolving resistant viral variants.…”
Section: Broadly Neutralizing Antibodies In Passive Immunization Trialsmentioning
confidence: 99%
“…While studying how efficacious are BnAbs, it is important to assess their behavior in vitro, the administration of BnAbs via intravenous therapy is not a feasible drug delivery system for large populations. It may also have limited use if administered in combination of BnAbs in high-risk groups, but overall this is not feasible or sustainable method for HIV-1 prevention [44].…”
Section: Broadly Neutralizing Antibodies In Passive Immunization Trialsmentioning
confidence: 99%
See 3 more Smart Citations